1. To solve the DE Bernoulli equation,
"dy\/dx = y(xy^6 - 1)"
The standard form is
"\\frac{dy}{dx}+P(x)y=f(x)y^n"
"Where" "n" "is" "not" "equal" "to" "zero" "or" "one"
"dy\/dx = xy^7 - y"
"dy\/dx+y = xy^7" "-------------->(1)"
"n=7"
"U=y^{1-n}=y^{1-7}=y^{-6}"
"U=y^{-6}"
"U^{-\\frac{1}{6}}=(y^{-6})^{-\\frac{1}{6}}" "\\implies" "y=U^{-\\frac{1}{6}}"
"dy\/dx =- \\frac{1}{6}U^{- \\frac{7}{6}}*\\frac{du}{dx}"
"\\frac{1}{6}U^{- \\frac{7}{6}}\\frac{du}{dx}+U^{-\\frac{1}{6}}=x U^{- \\frac{7}{6}}----------->(2)"
Multiply by "( \\frac{1}{6}U^{- \\frac{7}{6}})"
"\\frac{du}{dx}-6U^1=-6x"
"y(x)=\\epsilon^{\\int \\rho (x)dx}=\\epsilon^{\\int -6dx}= \\epsilon^{-6x}"
"\\implies y(x)=\\epsilon^{-6x}"
"\\epsilon^{-6x} \\frac{du}{dx}-6 \\epsilon^{-6x} U=-6x\\epsilon^{-6x}"
"\\frac{d}{dx}[\\epsilon^{-6x} U]=-6x\\epsilon^{-6x}"
Integration:
"\\epsilon^{-6x} U=\\int -6x\\epsilon^{-6x} dx"
"\\epsilon^{-6x} U=x\\epsilon^{-6x} +\\frac{1}{6}\\epsilon^{-6x} +C"
"\\implies U=x+\\frac{1}{6}+\\frac{C}{\\epsilon^{-6x} }"
"y^{-6}=x+\\frac{1}{6}+C\\epsilon^{6x} ------------->Answer"
2. To solve the DE Bernoulli equation.
"x \\frac{dy}{dx} + y = \\frac{1}{y^2}"
The standard form is
"\\frac{dy}{dx}+P(x)y=f(x)y^n"
Where n is not equal to zero or one
"\\frac{dy}{dx}+\\frac{1}{x}y=\\frac{1}{x}y^{-2}------------>(1)"
"n=-2"
"U=y^{1-n}=y^{1-(-2)}=y^3"
"U=y^{3}"
"\\implies y=U^{\\frac{1}{3}}"
"\\frac{dy}{dx}=\\frac{1}{3}U^{-\\frac{2}{3}}\\frac{du}{dx}"
"\\frac{1}{3}U^{-\\frac{2}{3}}\\frac{du}{dx}+\\frac{1}{x}U^{\\frac{1}{3}}=\\frac{1}{x}U^{-\\frac{2}{3}}------->(2)"
Multiply by "(3U^{-\\frac{2}{3}})"
"\\frac{du}{dx}+\\frac{3}{x}U^1=\\frac{3}{x}"
"y(x)=\\epsilon^{\\int \\rho (x)dx}=\\epsilon^{\\int \\frac{3}{x}dx}= \\epsilon^{3ln|x|}=|x^3|=x^3"
"\\implies y(x)=x^3"
"x^3\\frac{du}{dx}+3x^2U=3x^2"
"\\frac{d}{dx}[x^3U]=3x^2"
"x^3U=\\frac{3x^2}{3}+C"
"U=1+\\frac{C}{x^3}"
"y^3=1+\\frac{C}{x^x} \\implies y=(1+\\frac{C}{x^x})^{\\frac{1}{3}}------->Answer"
Comments
Leave a comment